If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + 16 = 7w Reorder the terms: 16 + 3w = 7w Solving 16 + 3w = 7w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-7w' to each side of the equation. 16 + 3w + -7w = 7w + -7w Combine like terms: 3w + -7w = -4w 16 + -4w = 7w + -7w Combine like terms: 7w + -7w = 0 16 + -4w = 0 Add '-16' to each side of the equation. 16 + -16 + -4w = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -4w = 0 + -16 -4w = 0 + -16 Combine like terms: 0 + -16 = -16 -4w = -16 Divide each side by '-4'. w = 4 Simplifying w = 4
| 12*x+6=-228 | | x*5+8=7 | | 8+2(8x-6)=16x+4 | | Xy+xz=1 | | f(x)=2x^2+12 | | 3x+32=56 | | 5(b+3)=3b+23 | | 3x-8=56 | | 4x+9-2x+2=3x-5-x | | 12-6x=2x+10 | | 11x+32=56 | | 3x-4=-x+6 | | U=5(6n+31)+9(n+1) | | 7x-2=3x-22 | | 40x+70y=6000 | | 3w+4=5m+7-m | | X+3x+2y= | | 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z |